â€œPENGARUH KUALITAS AUDIT TERHADAP MANAJEMEN LABA (STUDI PADA PERUSAHAAN SUB SEKTOR PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BEI TAHUN 2015)â€ - Krisdayanti, Krisdayanti (Jurusan Akuntansi, Fakultas Ekonomi dan Bisnis, Universitas Tanjungpura, 2017)
The purpose of this research is to analysis and provide empirical evidence about the relationship between audit quality on earnings management and answer the research result are inconsistent regarding the relationship between audit quality on earnings management. Auditor quality in this study use size of audit firm and industry specialist auditor. The modified Jones model is used to measure discretionary accruals (the proxi for earnings management). This study uses secondary data from annual reports of property and real estate sub sector companies which listed on Indonesia stock exchange (idx) in 2015. The method of data collection is purposive sampling method and resulted 39 firm observation. The analysis technique in this study uses a multiple regression analysis with help from a program named SPSS. The results indicate that audit firm size and industry specialist auditor had no significant effect to earnings management.Â Keywords: Audit quality, Earnings management, size of auditor firm, auditor industry specialization